PENGARUH KONSELING INDIVIDU TERHADAP IMPOSTOR PHENOMENON MAHASISWA UNIVERSITAS PGRI SUMENEP - Nismawati; Mafruhah; Astutik, Choli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of individual counseling on the impostor phenomenon and changes in the condition of students experiencing the impostor phenomenon before and after receiving individual counseling. This study used a quantitative experimental approach with a Paired Sample T-Test method. Data collection techniques used were questionnaires and observations. The data analysis technique used descriptive analysis and inferential analysis of the paired sample T-test to test the research hypothesis. The results showed that there were 15 students used as the research sample. Based on the data analysis technique using the Paired Sample T-test, a significance value (2-tailed) of 0.000 <0.05 was obtained. In this study, the researcher concluded that Ha was accepted and Ho was rejected, because there was an influence of variable X (Individual Counseling) on ​​variable Y (Impostor phenomenon) and there was a significant difference in the condition of students experiencing the impostor phenomenon before and after receiving individual counseling.